2023
DOI: 10.1007/s00262-023-03384-9
|View full text |Cite
|
Sign up to set email alerts
|

Immune-related toxicity and soluble profile in patients affected by solid tumors: a network approach

Abstract: Background Immune checkpoint inhibitors (ICIs) have particular, immune-related adverse events (irAEs), as a consequence of interfering with self-tolerance mechanisms. The incidence of irAEs varies depending on ICI class, administered dose and treatment schedule. The aim of this study was to define a baseline (T0) immune profile (IP) predictive of irAE development. Methods A prospective, multicenter study evaluating the immune profile (IP) of 79 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 87 publications
0
1
0
Order By: Relevance
“…A study by Tanaka et al noticed that increased IL6 levels post treatment were found in all 13 patients with malignant melanoma who received nivolumab and had irAEs, while 5 out of 7 patients who did not have irAEs had decreased IL6 levels [ 62 ]. Another study with 79 patients with solid tumors was performed using a 34-cytokine/chemokine assay and revealed a positive association between increased IL8, sLAG3, sPDL2, sHVEM, sCD137, sCD27, and sICAM-1 levels and the incidence of irAEs [ 63 ].…”
Section: Biomarkersmentioning
confidence: 99%
“…A study by Tanaka et al noticed that increased IL6 levels post treatment were found in all 13 patients with malignant melanoma who received nivolumab and had irAEs, while 5 out of 7 patients who did not have irAEs had decreased IL6 levels [ 62 ]. Another study with 79 patients with solid tumors was performed using a 34-cytokine/chemokine assay and revealed a positive association between increased IL8, sLAG3, sPDL2, sHVEM, sCD137, sCD27, and sICAM-1 levels and the incidence of irAEs [ 63 ].…”
Section: Biomarkersmentioning
confidence: 99%